2016
DOI: 10.17151/luaz.2016.43.4
|View full text |Cite
|
Sign up to set email alerts
|

Percepciones y reconocimiento local de fauna silvestre, municipio de Alcalá, departamento del Valle del Cauca, Colombia.

Abstract: En los Andes centrales de Colombia se documentaron las percepciones y reconocimiento local de aves, mamíferos, anfibios y reptiles. Se entrevistó a campesinos con edad superior a 30 años para situar áreas de hábitat y reconocer especies en usos y coberturas del terreno. El reconocimiento de los agricultores se tradujo por los investigadores-mediadores en la formulación de categorías taxonómicas con visitas a los predios, avistamiento y la ayuda de guías de campo. Se reconocieron 168 especies: 103 de aves, 31 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…The species with the highest use and importance for the community of Bonifacio García because they have a high (0.19) medicinal diversity value (VDM) were the iguana Ctenosaura pectinata, whitetail deer Odoicoileus virginianus and rattlesnake Crotalus culminatus, this because each one of them is used in the treatment of 3 diseases; this is different to what García et al (2017) report, as those authors mention the skunk as the animal with the highest index (0.6) for Zacualpan de Amilpas, Morelos, Mexico. Enríquez et al (2006) mention that the most important species are those that help for an specific disease, that is, with a lower VDM, which in the case of the community under study includes the following species: armadillo Dasypus novemcinctus, species used to treat cough, fact that is different from what is reported in Colombia where it is employed to manage asthma (Aldana et al 2016).…”
Section: Resultsmentioning
confidence: 97%
“…The species with the highest use and importance for the community of Bonifacio García because they have a high (0.19) medicinal diversity value (VDM) were the iguana Ctenosaura pectinata, whitetail deer Odoicoileus virginianus and rattlesnake Crotalus culminatus, this because each one of them is used in the treatment of 3 diseases; this is different to what García et al (2017) report, as those authors mention the skunk as the animal with the highest index (0.6) for Zacualpan de Amilpas, Morelos, Mexico. Enríquez et al (2006) mention that the most important species are those that help for an specific disease, that is, with a lower VDM, which in the case of the community under study includes the following species: armadillo Dasypus novemcinctus, species used to treat cough, fact that is different from what is reported in Colombia where it is employed to manage asthma (Aldana et al 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Registro del conocimiento local tomando en cuenta el uso y percepción sobre las especies silvestres (Aldana et al, 2016;Díaz y Moreno, 2003;Chacón y Salcedo, 2017).…”
Section: Estímulos Visualesunclassified
“…The bush is the main space where appropriation takes place, as it is the natural environment inhabited by the species. López et al (2018) identified 11 hunting spaces in Guerrero, which indicates that the inhabitants travel long distances and possess knowledge of their environment that allows them to obtain bush meat (Aldana et al 2016;Tamburini et al 2016;Estrada et al 2018;López et al 2018;García et al 2020).…”
Section: Hunting Areasmentioning
confidence: 99%